Karen Bray, Heather Eaton, and Whitney Bauman (eds.), "Earthly Things: Immanence, New Materialisms, and Planetary Thinking" - Dragt, Kennedy (Journal for the study of religion, nature and culture, 2025)
Karen Bray, Heather Eaton, and Whitney Bauman (eds.), Earthly Things: Immanence, New Materialisms, and Planetary Thinking (New York: Fordham University Press, 2023), 352 pp, $ 40 (pbk), ISBN: 9781-5315-0306-2.